Why Tackling Energy Governance in Developing Countries Needs a Different Approach - McCulloch, Neil (The Policy Practice & Chemonics, 2021)
Global efforts to improve energy access and quality and to tackle climate change need a different approach to addressing poor energy governance. In 2015, leaders from around the world agreed to 17 Sustainable Development Goals (SDGs) to be achieved by 2030.1 The seventh goal (SDG7) is “Ensure access to affordable, reliable, sustainable and modern energy for all.” In the same year, the world’s leaders concluded the Paris Agreement to tackle climate change, which will require a global transition of the energy sector away from the use of fossil fuels. Yet, in many developing countries, despite growing investments in clean energy, the transition is happening much more slowly than needed to achieve SDG7 and avert damaging climate change. The central reason for this is poor energy governance. This paper outlines the size and nature of the energy challenge, with a focus on electricity. It describes the investments that are currently being made to improve the quality of power and access to electricity — and the growing evidence that investments often fail due to poor energy governance. The paper then delves more deeply into how bad governance influences the quality of and access to electricity, with specific country examples. It shows the importance of understanding how electricity fits into the political settlement of a country and how this affects the incentives of key actors in the sector. Unfortunately, donor projects designed to widen electricity access or to support reform of the power sector in developing countries often pay too little attention to the problem’s political nature; the same is true of measures to improve energy efficiency or to promote renewables. The paper outlines a new way of thinking about energy governance and shows how interventions can be better matched to the different governance challenges that they face. It concludes with recommendations for donors on how energy programs can be better designed and procured — as well as recommendations for implementors on how to improve the chances of successful implementation by adapting to the political realities of the contexts in which they operate.

Energy Governance in Developing Countries — A New Approach - Mcculloch, Neil (The Policy Practice & Chemonics, 2021)
In 2015, leaders from around the world agreed to 17 Sustainable Development Goals (SDGs) to be achieved by 2030. The seventh goal (SDG7) is: “Ensure access to affordable, reliable, sustainable and modern energy for all.” In the same year, the world’s leaders concluded the Paris Agreement to tackle climate change, which will require a global transition in the energy sector away from the use of fossil fuels. Yet, despite growing investments in clean energy in many developing countries, the transition is happening much more slowly than needed. The central reason for this is poor energy governance. This technical brief shows how poor energy governance damages energy access and efforts to improve the quality and reliability of power. It explains the political reasons why energy governance is so bad in many countries and contrasts this with the current system of procuring technical assistance, which largely ignores the energy governance challenge. It shows that a new approach to tackling energy governance is emerging that is better matched to the nature of the problems faced and provides recommendations on how to implement it.

Bringing adaptive management to life: Insights from practice - Arora, Anmol; Gogoi, Elizabeth; Joy, Divya; Kumar, Pankaj; Luthra, Rajni; Pal, Uma; Pervaiz, Arif (Oxford Policy Management, 2019)

A Guide to Assessing the Political Economy of Domestic Climate Change Governance - Worker, Jesse; Palmer, Niki (World Resources Institute, 2021)
This paper discusses how understanding the domestic political economy of climate governance is critical for developing informed strategies to build and sustain political ambition. It provides guidance and a methodology for domestic stakeholders to determine the types of institutional reforms, incentives, coalitions, and policy design that can entrench long-term political support for climate ambition. The assessment can also help users identify political barriers to more equitable climate action and identify reforms that may strengthen inclusion and accountability. EXECUTIVE SUMMARY Highlights ▪ There is overwhelming evidence of the social, economic, and environmental case to reduce greenhouse gas (GHG) emissions and rapidly scale up adaptation. Yet, despite a proliferation of climate laws and policies over the last 10–15 years, emissions are still rising, and adaptation needs remain urgent. ▪ This calls for a more sophisticated assessment of the political economy factors that may enable or constrain implementation of policies and actions and sustain political commitment at the country level. ▪ This guide offers an assessment methodology to understand how structural factors, rules and norms, stakeholders and interests, and ideas and narratives influence the political economy of climate action in a given country context. ▪ The methodology was developed on the basis of climate policy, governance, and political economy literature with contributions from subject matter experts. ▪ We intend the assessment to support civil society coalitions, reform-minded civil servants and politicians, international organizations, and other stakeholders. ▪ The resulting analysis should deepen the understanding of context while informing the advocacy, policy design, coalition building, capacity building, and communications of domestic stakeholders.